2002
DOI: 10.1021/ja0265409
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Proximal Hydrogen Bonding Network in Cytochrome P450cam-Catalyzed Oxygenation

Abstract: Structural and functional roles of the hydrogen bonding network that surrounds the heme-thiolate coordination of P450(cam) from Pseudomonas putida were investigated. A hydrogen bond between the side chain amide of Gln360 and the carbonyl oxygen of the axial Cys357 was removed in Q360L. The side chain hydrogen bond and the electrostatic interaction between the polypeptide amide proton of Gln360 and the sulfur atom of Cys357 were simultaneously removed in Q360P. The increased electron donation of the axial thiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
145
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(166 citation statements)
references
References 55 publications
20
145
1
Order By: Relevance
“…Reactivity of Oxy-P450cam with Electron Donors-Besides the enhanced push effect in the L358P mutant (16,17), our current NMR data show that both D-camphor and the ␤-proton of the axial Cys approach closer to the heme-iron as observed in the Pdx-bound wild type enzyme. Therefore, we expected that the mutant should exhibit functional properties characteristic of Pdx-bound P450cam.…”
Section: Heme Environment Of the Ferrous-co Form Of L358p-up-mentioning
confidence: 50%
See 1 more Smart Citation
“…Reactivity of Oxy-P450cam with Electron Donors-Besides the enhanced push effect in the L358P mutant (16,17), our current NMR data show that both D-camphor and the ␤-proton of the axial Cys approach closer to the heme-iron as observed in the Pdx-bound wild type enzyme. Therefore, we expected that the mutant should exhibit functional properties characteristic of Pdx-bound P450cam.…”
Section: Heme Environment Of the Ferrous-co Form Of L358p-up-mentioning
confidence: 50%
“…Here, in order to confirm that the Pdx-induced structural changes can be the trigger for the turnover reaction, we focused on a P450cam mutant, Leu-358 3 Pro mutant (L358P) (16,17), whose spectroscopic properties are similar to those of wild type P450cam in the presence of Pdx. Earlier work (16,17) showed that mutating Leu-358 to Pro in P450cam disrupts the hydrogen bond between the amide proton of the main chain and the axial thiolate (Fig. 1), and leads to enhanced -electron donation from the axial thiolate to the heme iron, which changes Fe-CO and C-O in the ferrous-CO form (Table I).…”
mentioning
confidence: 99%
“…The enhancement of the electronic donation from the axial Cys, referred to as the enhanced "push effect," was believed to facilitate the heterolysis of molecular oxygen bound to the heme-iron (58). The P450cam mutant, Leu-358 3 Pro, whose Fe-CO and FeC-O Raman lines indicated up-shift and down-shift, respectively, as found for wild-type P450cam in the presence of Pdx, exhibited the high oxygen activation activity, confirming that the O-O bond scission is accelerated by the enhanced push effect (36,58,59). The Pdx-induced conformational changes at the proximal side of the heme, therefore, substantially contribute to the activation of molecular oxygen on the heme-iron in P450cam.…”
Section: Significance Of the Pdx-induced Conformational Changes On P4mentioning
confidence: 73%
“…This effect is also seen in model compounds with a thiolate ligand to iron (39). The protein-derived hydrogen bonds to the axial thiolate ligand to iron in P450cam have been shown to affect the OOO bond cleavage (40).…”
Section: Oxygen Activation By Heme Proteinsmentioning
confidence: 86%